2007
DOI: 10.1021/ja0647194
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of Alkynes Promoted by a Pincer-Ligated Iridium Complex. C−C Reductive Elimination Inhibited by Steric Crowding

Abstract: The pincer-ligated species (PCP)Ir (PCP = kappa3-C6H3-2,6-(CH2PtBu2)2) is found to promote dimerization of phenylacetylene to give the enyne complex (PCP)Ir(trans-1,4-phenyl-but-3-ene-1-yne). The mechanism of this reaction is found to proceed through three steps: (i) addition of the alkynyl C-H bond to iridium, (ii) insertion of a second phenylacetylene molecule into the resulting Ir-H bond, and (iii) vinyl-acetylide reductive elimination. Each of these steps has been investigated, by both experimental and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 75 publications
5
83
0
1
Order By: Relevance
“…IIIa ! IV), which also proceeds through the sequence of RaH bond oxidative addition, alkyne insertion into the MaH bond of VI and reductive elimination (M ¼ Ru, Rh, Ir) [38][39][40][41][42][43].…”
Section: Catalytic CXC Bond Formation Via the Reductive Elimination Pmentioning
confidence: 99%
“…IIIa ! IV), which also proceeds through the sequence of RaH bond oxidative addition, alkyne insertion into the MaH bond of VI and reductive elimination (M ¼ Ru, Rh, Ir) [38][39][40][41][42][43].…”
Section: Catalytic CXC Bond Formation Via the Reductive Elimination Pmentioning
confidence: 99%
“…We have also found that the Ir-H bond resulting from alkynyl C-H addition could add across an acetylene triple bond to give a vinyl-alkynyl iridium complex that undergoes C-C elimination to give the corresponding enyne [10]. This led us to study C-C elimination from a range of complexes (PCP)IrRR [30].…”
Section: Introductionmentioning
confidence: 97%
“…Our group has largely focused on pincer-iridium complexes, which have shown a strong tendency toward the activation of C-H bonds. These complexes have been found to effect the oxidative addition of a variety of C-H bonds including those with sp 2 -and sp-hybridized carbon [8][9][10]. Most notable, however, has been the activation of C(sp 3 )-H bonds, leading to alkane dehydrogenation [6,7].…”
mentioning
confidence: 99%
“…Reversible hydride insertion into alkynes is rare. 21 These observations combine to suggest that 7 is the resting state. Under this assumption that hydride insertion into the alkyne is irreversible, the observation of a species consistent with acyl-hydride 5 as an intermediate, rather than 6b, suggests that it precedes the turnover-limiting step.…”
mentioning
confidence: 94%